The Role of Financial Literacy and Investment Interest in Capital Market Investment Decisions Among Generation Z - Satria Saputra; Doly Nofiansyah; Melia Frastuti (Equivalent : Journal of Economic, Accounting and Management, 2026)
The rapid growth of Generation Z investors in Indonesia's capital market has increased the importance of understanding the factors influencing investment decisions. However, previous studies have reported inconsistent findings regarding the role of financial literacy in shaping investment decisions, indicating the need for further empirical investigation. This study aims to analyze the influence of financial literacy and investment interest on capital market investment decisions among Generation Z. A quantitative approach with an explanatory research design was employed. The study involved 60 students from the Faculty of Islamic Business, Universitas Indo Global Mandiri, selected using purposive sampling. Primary data were collected through structured questionnaires and analyzed using multiple linear regression with SPSS Statistics 25. The findings reveal that financial literacy does not have a significant effect on investment decisions, indicating that knowledge alone is insufficient to encourage Generation Z to invest in the capital market. In contrast, investment interest has a positive and significant influence on investment decisions, suggesting that individuals with stronger investment interest are more likely to make actual investment decisions. These findings imply that enhancing investment participation among Generation Z requires not only improving financial literacy but also fostering investment motivation through financial education, digital investment platforms, and practical investment experiences. This study contributes to the literature by providing empirical evidence on the dominant role of investment interest in shaping investment decisions among Generation Z in the Indonesian capital market. Abstrak  Pesatnya pertumbuhan investor Generasi Z di pasar modal Indonesia meningkatkan pentingnya memahami faktor-faktor yang memengaruhi keputusan investasi. Namun, penelitian terdahulu masih menunjukkan hasil yang beragam mengenai peran literasi keuangan terhadap keputusan investasi sehingga diperlukan kajian empiris lebih lanjut. Penelitian ini bertujuan menganalisis pengaruh literasi keuangan dan minat berinvestasi terhadap keputusan investasi pasar modal pada Generasi Z. Penelitian menggunakan pendekatan kuantitatif dengan desain explanatory research. Sampel penelitian berjumlah 60 mahasiswa Fakultas Bisnis Syariah Universitas Indo Global Mandiri yang dipilih menggunakan teknik purposive sampling. Data primer dikumpulkan melalui kuesioner terstruktur dan dianalisis menggunakan regresi linear berganda dengan bantuan SPSS Statistics 25. Hasil penelitian menunjukkan bahwa literasi keuangan tidak berpengaruh signifikan terhadap keputusan investasi, yang mengindikasikan bahwa pengetahuan keuangan saja belum cukup mendorong Generasi Z untuk berinvestasi di pasar modal. Sebaliknya, minat berinvestasi berpengaruh positif dan signifikan terhadap keputusan investasi, sehingga menjadi faktor yang lebih dominan dalam mendorong perilaku investasi. Temuan ini menunjukkan bahwa peningkatan partisipasi investasi Generasi Z tidak hanya memerlukan penguatan literasi keuangan, tetapi juga strategi yang mampu meningkatkan minat berinvestasi melalui edukasi keuangan, pemanfaatan platform investasi digital, dan pengalaman investasi yang berkelanjutan. Penelitian ini memberikan kontribusi empiris terhadap pengembangan literatur mengenai perilaku investasi Generasi Z di pasar modal Indonesia.